The Role of Leadership in Driving Organizational Innovation and Adaptation in the Era of Technological Disruption - Wijaya, Ayi Supardi Ganda (Pascasarjana Universitas Pasundan, 2024)
In the era of rapid technological disruption, the role of leadership is crucial in driving organizational innovation and adaptation. As technologies such as artificial intelligence (AI), blockchain, and the Internet of Things (IoT) evolve, many industries are undergoing profound changes in the way they operate. These disruptive technologies present not only challenges but also vast opportunities for companies that can innovate and adapt quickly. Visionary and adaptive leadership is essential for guiding organizations through these changes and ensuring their continued relevance in a competitive global market. This study aims to explore how leadership influences an organization's ability to navigate technological disruption and foster sustainable innovation processes. Additionally, this research will examine the challenges faced by leaders in leveraging disruptive technologies to create competitive advantages. The findings are expected to provide valuable insights for business leaders and decision-makers in formulating effective strategies in an ever-evolving technological landscape.